Incidence and distribution of malignant solid tumors in children 0-15 years, by histological type, age and gender (Revista Venezolana de Salud Pública, 2018)
This work aims to determine the frequency and distribution of malignant solid tumors in children aged 0-15 years, according to histological type, age and sex. Review of 17 years in the Department of Pathology, " Dr. Hans R. Döehnert” Central Hospital" Antonio Maria Pineda " during the years 1986-2003. Transverse retrospective descriptive non-experimental study was performed 247 biopsies from patients with diagnosis is a malignant solid tumor in the pathology department, " Dr. Hans R. Döehnert” university central hospital “Antonio Maria Pineda” from 1986 to 2003. Lymphomas ranked first with 76 cases (30,76 %) non-Hodgkin lymphomas , 46 cases (18,62 %) , Hodgkin's disease 30 cases (12,14 %) , second tumors are Central Nervous System (CNS ) : 33 cases ( 13,36 %), then the neuroblastomas : 30 cases (12,14 %) , Nephroblastoma ( Wilms tumor ) : 22 cases ( 8,90 %), osteosarcomas 18 cases ( 7,28% ) , Rhabdomyosarcomas : 17 cases ( 6,88 %) , germ cell tumors 10 cases ( 4,84 %) , Retinoblastoma 9 cases ( 3,64 %) , and round cell tumors 7 cases ( 2,83 ) , Ewing sarcoma 5 cases ( 2,02 %) , non-gonadal teratomas (immature ) 4 cases ( 1,60 %) , hepatoblastoma  4 patients ( 1,60 %) , Stromal cell tumors and Sex Cord 3 cases ( 1,21 %) , thyroid carcinoma 2 cases (0,80 % ) , colon adenocarcinoma 2 cases (0,80 % ), melanoma 1 case ( 0,40 %) , histiocytosis one case ( 0,40 % ) , clear cell sarcoma of kidney a case ( 0,40 % ) , hemangiopericytoma one case ( 0,40 % ) , malignant schwannoma one case ( 0,40 %). In children aged 2-6 years were more frequent lymphomas and nephroblastoma and neuroblastoma. In children aged 10-12 years were Rhabdomyosarcomas and osteosarcomas , with a predominance in males (59,6%). The most frequent solid tumors are malignant lymphomas , followed by CNS tumors , the most affected age group is between 2 and 6 years, with a predominance in males.
Keywords: Pediatric cancer; Cancer distribution; malignant tumor; frequency